Evolutionary history and patterns of geographical variation, fertility, and hybridization in Stuckenia (Potamogetonaceae) - Fehrer, Judith; Nagy Nejedlá, Michaela; Hellquist, C. Barre; Bobrov, Alexander A.; Kaplan, Zdenek (Frontiers in Plant Science, 2022)
Aquatic plant species are often widespread even across continents. They pose a challenge to species delimitation and taxonomy due to their reduced morphology and high phenotypic plasticity. These difficulties are even more pronounced in the case of interspecific hybridization. We investigate the aquatic plant genus Stuckenia for the first time on a worldwide scale. Expert species determination is aided by sequencing of nuclear ribosomal ITS and 5S-NTS regions and the plastid intergenic spacers rpl20-5’rps12 and trnT-trnL. Nuclear markers are used to infer hybridization, and the maternal origin of hybrids is addressed with plastid markers. Pure species are subjected to phylogenetic analyses. Two main Stuckenia lineages are found, one consists of S. amblyphylla, S. filiformis, S. pamirica and S. vaginata, the other of S. pectinata and S. striata. The widespread species S. pectinata, S. filiformis and S. vaginata show intraspecific genetic variation, which is structured geographically. Many intraspecific hybrids, which are usually fertile, occur between those genotypes. Interspecific hybrids, which are consistently sterile, are detected among all widespread species; some are reported for the first time in several countries and regions. They originated multiple times from reciprocal crosses and reflect the geographic origins of parental genotypes. Intraspecific genetic variation can be higher than interspecific differences between closely related species. Comparison of phenotypic variation in the field and in cultivation with genotypic variation shows that numerous conspicuous forms have been overestimated taxonomically. These are resolved as phenotypes responding to unusual environments, have recurrently evolved adaptations, or represent extreme forms of continuous variation of the recognized species. However, some specific regional lineages, which have evolved from variable species, may be interpreted as early steps of the speciation process. Hybridization has been underestimated in some regions as a source of Stuckenia diversity, and the respective hybrid plants have been misidentified as intraspecific taxa or even as separate species. Many erroneous entries in sequence databases are detected and summarized. This work provides a sound basis for species delimitation and hybrid recognition in this difficult genus.